Clinical Epidemiology, Evidence Based Medicine and Good Clinical Practice Guidelines vs. Clinical Method? - Luis Alberto Corona Martínez; Mercedes Fonseca Hernández (Medisur)
Evidence Based Medicine, as a trend or approach to the medical practice nowadays, and the use of Good Clinical Practice Guidelines in the assistance activities are core elements that contribute to improve the professional practice and the decision making process in diagnosis and therapy; but they do not substitute the professional method for patients assistance: the clinical method. The purpose of this article is to analyze the role of clinical epidemiology, evidence based medicine and good clinical practices guidelines in the decision making process, as well as the relation established between those and the clinical method.